2017
DOI: 10.1111/tan.13146
|View full text |Cite
|
Sign up to set email alerts
|

Candidate gene molecular markers as tools for analyzing genetic susceptibility to morbillivirus infection in stranded Cetaceans

Abstract: Morbilliviruses, such as Cetacean morbillivirus (CeMV) or Phocine distemper virus (PDV), represent a growing threat for marine mammals on both hemispheres. Because free-ranging animal populations strongly rely on natural resistance mechanisms, innate immunity-related genes and virus cell entry receptor genes may represent key factors involved in susceptibility to CeMV in Cetaceans. Using the next generation sequencing technology, we have sequenced 11 candidate genes in two model species, Stenella coeruleoalba … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Roles for MHC class I can also serve as an inhibitory ligand for natural killer cells and this mechanism can be exploited by viruses, which can inhibit various stages of the MHC class I antigen presentation pathway for immune evasion [71][72][73] as well as by some cancer cells, which can downregulate MHC I to avoid normal immune surveillance [74][75]. MHC I has been studied in harbour seal [76], with possible variation suggested in immune response genes in relation to susceptibility to phocine distemper virus [77] and with respect to morbillivirus infection in stranded cetaceans [78].…”
Section: Discussionmentioning
confidence: 99%
“…Roles for MHC class I can also serve as an inhibitory ligand for natural killer cells and this mechanism can be exploited by viruses, which can inhibit various stages of the MHC class I antigen presentation pathway for immune evasion [71][72][73] as well as by some cancer cells, which can downregulate MHC I to avoid normal immune surveillance [74][75]. MHC I has been studied in harbour seal [76], with possible variation suggested in immune response genes in relation to susceptibility to phocine distemper virus [77] and with respect to morbillivirus infection in stranded cetaceans [78].…”
Section: Discussionmentioning
confidence: 99%
“…At least 29 genes have been proposed to potentially play a role in immune responses to morbilliviruses in general (Hashiguchi et al, 2011; Haralambieva et al, 2015; McCarthy et al, 2011; Stejskalova et al, 2017), but only three of these ( PATJ , MAPK8 and IL4α ) were found to be under putative selection between cases and controls in this study. For the remaining 26 genes, 22 aligned to the SABD reference genome.…”
Section: Resultsmentioning
confidence: 59%
“…At least 29 genes have been proposed to potentially play a role in immune responses to morbilliviruses in general (Hashiguchi et al, 2011;Haralambieva et al, 2015;McCarthy et al, 2011;Stejskalova et al, 2017), but only three of these (PATJ, MAPK8 and IL4α) were found to or enhancer regions of the genes. The majority of the 22 genes were highly polymorphic (Table S7); however, inspection of genotype counts for the top performing SNP within each gene (i.e., SNP with greatest allele frequency differences between cases and controls) highlighted a lack of heterozygosity within 11 of the immune genes across all samples (Figure 3, Table S7).…”
Section: Candidate Immune Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural infection of seals with CeMV; however, has rarely been documented. This suggests that host factors other than SLAMs are involved in the host–virus specificity of morbilliviruses [175,176]. In addition, ecological factors that facilitate contact of host animals may be a key factor in determining morbillivirus host specificity.…”
Section: Interaction Between Slam and The Viral H Proteinmentioning
confidence: 99%